Religion and the civilizational process: The civilizing role of religion in the socio-political decision making process in pre-colonial Ibo community of Nigeria - Owoyemi, Musa Yusuf (Universiti Kebangsaan Malaysia, 2012)
This paper looks at the role of religion in the socio-political decision making processcs and the organization of the Ibo community - in a rational or systematic way-along this line, before the incurtion of the colonial masters into their community, as well as the enforcement of these decisions through religion and its relevance to the contemporary time. Using the historical and analytical method, the paper delved into the history of the Ibos the arrangement and organization of the community from the little unit of the family setup to the complex whole of the community and how they are managed by those saddled with authority as well as the decision making processes in a democratic way right from the family unit to the complex whole of the larger community. The role of religion in this whole process and how it helps cement and enforce the rational organization and decision making processes of the community was also analyzed.Finally, the paper contrast this process with that of the present modern time in which religion has been relegated to the background and removed from the civilizational processes of the contemporary time. Thus, it concludes that religion, despite the negativity that is ascribed to it today in the modern world.could be a useful tool in any civilizational process because, when properly harnessed by the people, it selves as a stabilizing force in the society and, contrary to popular belief, it is not opposed to scientific and rational processes.